Comportamento ingestivo de novilhos de corte sob diferentes alturas de pastejo do capim Tanzânia1 - Barbero, Rondineli Pavezzi [UNESP]; De Freitas Barbosa, Marco Aurélio Alves; De Castro, Letícia Maria; De Azambuja Ribeiro, Edson Luis; Mizubuti, Ivone Yurika; Massaro Jr., Fernando Luiz; Da Silva, Leandro Das Dores Ferreira (Universidade Estadual de Londrina, 2012)
Ingestive behavior of steers grazing in four heights of Tanzânia grass was evaluated. 12 paddocks of one hectare each, with three replicates for each height, and three males Nelore cattle, per paddock, more regulators at the time, were used. Time and time daytime grazing, ruminating and resting, rate of eating and rumination, length of grazing cycles and rumination, were observed. Forage samples were collected at ground level and grazing simulation to assess possible selectivity. The experimental design was completely randomized, and analysis of variance was performed for continuous variables to regression procedures, and discrete variables in tests of means (P < 0.05). The highest heights had high bit rates, while the smallest was higher expenditure of time in search for forage mass. Grazing time decreased linearly as increased the canopy height, however the opposite was observed for rumination. At all canopy heights was observed selectivity of forage for the animals.
Ingestive behavior of steers grazing under different heights of Tanzânia grass
Keywords: Bit rate; Idleness; Rumination